2012
DOI: 10.1128/jcm.00224-12
|View full text |Cite
|
Sign up to set email alerts
|

Use of Matrix-Assisted Laser Desorption Ionization–Time of Flight Mass Spectrometry for Caspofungin Susceptibility Testing of Candida and Aspergillus Species

Abstract: Matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS) was evaluated for testing susceptibility to caspofungin of wild-type and fks mutant isolates of Candida and Aspergillus. Complete essential agreement was observed with the CLSI reference method, with categorical agreement for 94.1% of the Candida isolates tested. Thus, MALDI-TOF MS is a reliable and accurate method to detect fungal isolates with reduced caspofungin susceptibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
116
0
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 124 publications
(124 citation statements)
references
References 29 publications
1
116
0
7
Order By: Relevance
“…A panel of 65 C. albicans isolates with and without FKS1 gene (which encodes ␤-1,3-glucan synthase [GS], the echinocandin target) mutations that are known to be associated with resistance to CSF (25,26) were included in the study (see Table S1 in the supplemental material). Ten fks1 mutant isolates were previously investigated (19). Before testing, each isolate was subcultured onto Sabouraud dextrose agar to ensure its purity and viability and reidentified by standard methods.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…A panel of 65 C. albicans isolates with and without FKS1 gene (which encodes ␤-1,3-glucan synthase [GS], the echinocandin target) mutations that are known to be associated with resistance to CSF (25,26) were included in the study (see Table S1 in the supplemental material). Ten fks1 mutant isolates were previously investigated (19). Before testing, each isolate was subcultured onto Sabouraud dextrose agar to ensure its purity and viability and reidentified by standard methods.…”
Section: Methodsmentioning
confidence: 99%
“…Isolates were categorized as susceptible, intermediate, or resistant on the basis of the new CLSI breakpoints for CSF and C. albicans that were set at Յ0.25 g/ml (susceptible), 0.5 g/ml (intermediate), and Ն1 g/ml (resistant) (26). AFST by MALDI-TOF MS (ms-AFST) was performed according to our published method (19). Briefly, protein extracts were prepared from fungal isolates (starting from an inoculum of 1 ϫ 10 7 CFU/ml) grown in RPMI broth containing serial dilutions (ranging from 0.5 to 0.004 g/ml) or a breakpoint concentration (intermediate, 0.03 g/ml) of CSF (pure substance provided by Merck, Milan, Italy) at 37°C under agitation for 15 or 3 h, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, several studies have already demonstrated the reliability of MALDI-TOF MS in the rapid identification of yeasts in different clinical settings (5-7), evidencing its cost-effectiveness in allowing the initiation of species-targeted antifungal therapy (7)(8)(9). To date, four MALDI-TOF MS systems are commercially available: the Microflex LT Biotyper (Bruker Daltonics, Bremen, Germany) (BMS), the Saramis system (bio-Mérieux, Marcy l'Etoile, France), the Vitek MS system (bioMérieux, Marcy l'Etoile, France) (VMS), and, very recently, the Andromas system (Andromas, Paris, France).…”
mentioning
confidence: 99%